2010
DOI: 10.1097/iae.0b013e3181e3790b
|View full text |Cite
|
Sign up to set email alerts
|

Grading Diabetic Retinopathy Severity From Compressed Digital Retinal Images Compared With Uncompressed Images and Film

Abstract: Full Early Treatment Diabetic Retinopathy Study scale DR severity level grading using C images is comparable to that using U images or film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…This level of compression has not been shown to lose any clinically significant information [1315]. …”
Section: Stages In the Development Of The English Nhs Diabetic Eye Scmentioning
confidence: 99%
“…This level of compression has not been shown to lose any clinically significant information [1315]. …”
Section: Stages In the Development Of The English Nhs Diabetic Eye Scmentioning
confidence: 99%
“…7 One study found no differences between uncompressed and compressed images of diabetic retinopathy when JPEG2000 compression was used at a ratio of 37 to 1. 8 Another study also found no differences in diagnostic accuracy with a compression factor of 30 but determined the reproducibility of diagnostic judgment was greater with images uncompressed. 9 Fourteen percent of diagnoses were adversely affected by picture quality in a videoconferencing study, 10 whereas other studies indicate video quality may be inadequate for some exams 11 and inferior to still images.…”
Section: Compressed Videomentioning
confidence: 98%
“…Li et al [8] performed a study in which variants of digital implementation were compared with film-based ETDRS color 7SF photography as the reference standard. Variations included digital color 7SF photography in three formats (with no file compression, with file compression [35], and with stereo effect removed [36]) and digital wide-angle nine-field photography integrated into a mosaic. They found that the variability between gradings of digital variants and the film reference, taking the median of three independent gradings, was no greater than the variability between the individual graders within each of the media.…”
Section: Continuity and Standardization Of Image Data In Research Andmentioning
confidence: 99%